Existence Of Human Being As Reflected In Ernest Hemingway's The Old Man And The Sea Novel (1952): An Existentialist Approach - Rinna, Gendhis Af; , Titis SetyaBudi, S. S., M.Hum (2017)
This study is about human existence. This study is proposed to reveal how existence of human is reflected in The Old Man and The Sea (1952) novel by Ernest Hemingway. This study is also expected to give the paedagogical implication based on the context of literary study. The aims of this research are to find out the existence of Santiago, the cause and the effect of human's existence. The object of this study is Ernest Hemingway's The Old Man and The Sea novel. The research uses existentialist approach. This study employs qualitative research. In this method, there are two types of data source, namely primary and secondary data. The primary is about the novel itself. Then the secondary data are taken from other sources which are related to the primary data such as articles, website, journal, and some books dealing with the research. The technique of data collection is library research. The technique of data analysis is descriptive qualitative research. Based on the existentialist analysis, existence of human being can be shown from first, The Old Man and The Sea novel wants to describe Santiago as brave, persistent, opinionated, and socializing. The Old Man and The Sea novel wants to reflect the human existence happening to Santiago. The researcher is found that human attains their existence through the stages of life's way which is divided into three stages; they are aesthetic, ethical, and religious. The effect of human existence reflects in The Old Man and The Sea novel (1952) by Ernest Hemingway.